PELAKSANAAN PENGEMBALIAN KELEBIHAN PEMBAYARAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KOTA PONTIANAK - NIM. A1011211103, ELSA MAULI TAUFIK (Jurnal Fatwa Hukum, 2025)
Abstract  Land and Building Rights Acquisition Duty (BPHTB) is a tax imposed on the acquisition of land and or building rights. BPHTB is a tax that adheres to the payment system self assessment so that in its implementation, it is prone to miscalculation that results in taxpayers overpaying or underpaying taxes that should be owed. The formulation of the problem in this study is how the procedure for returning BPHTB overpayment in Pontianak City and what obstacles are faced by the Pontianak City Bapenda in the implementation of BPHTB overpayment refund. The purpose of the study is to find out the procedure for refunding overpayment of BPHTB for taxpayers in Pontianak City and to find out the obstacles faced by the Pontianak City Bapenda in the implementation of the refund of overpayment of BPHTB.The research method used by the author is juridical-empirical. In this writing, the author uses primary data and secondary data. The author uses interview techniques as a way to obtain primary data, using documentation techniques to browse library materials in the form of Mayor Regulation Number 80 of 2020 concerning Procedures for Returning Overpayment of Regional Taxes and Regional Levies. The interview was conducted with Employees of the Regional Tax and Levy Planning and Development Division of the Pontianak City Regional Revenue Agency and BPHTB Management Field Staff of the Notary Office Budi Prasetiyono, S.H.The results of the analysis of this study are that the Pontianak City Regional Revenue Agency has not implemented the return of the 2024 BPHTB overpayment to Taxpayers due to the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, which was newly enacted in January 2024. However, when viewed from the perspective of legal science, we know the principle of non-retroactivity. The non-retroactive principle states that the law does not apply retroactively, so that the renewal of regulations has no connection with the non-realization of the return of BPHTB overpayment by Pontianak City taxpayers.  Keywords:       BPHTB       Overpayment       Refund,       Tax,       Pontianak       City      AbstrakBea Perolehan Hak atas Tanah dan Bangunan (BPHTB) merupakan pajak yang dikenakan atas perolehan hak atas tanah dan atau bangunan. BPHTB merupakan pajak yang menganut sistem pembayaran self assessment sehingga dalam pelaksanaannya rentan terjadi kesalahan perhitungan sehingga mengakibatkan Wajib Pajak kelebihan atau kurang membayar pajak yang seharusnya terhutang. Rumusan masalah dalam penelitian ini adalah bagaimana prosedur pengembalian kelebihan pembayaran BPHTB di Kota Pontianak serta apa kendala yang dihadapi pihak Bapenda Kota Pontianak dalam pelaksanaan pengembalian kelebihan pembayaran BPHTB. Tujuan penelitian untuk mengetahui prosedur pengembalian kelebihan pembayaran BPHTB wajib pajak di Kota Pontianakdan untuk mengetahui kendala yang dihadapi Bapenda Kota Pontianak dalam pelaksanaan pengembalian kelebihan bayar BPHTB.Metode penelitian yang penulis gunakan adalah yuridis-empiris. Dalam penulisan ini, penulis menggunakan data primer dan data sekunder. Penulis menggunakan teknik wawancara sebagai cara memperoleh data primer, menggunakan teknik dokumentasi untuk menelusuri bahan Pustaka berupa Peraturan Wali Kota Nomor 80 Tahun 2020 tentang Tata Cara Pengembalian Kelebihan Pembayaran Pajak Daerah dan Retribusi Daerah. Wawancara dilakukan bersama Pegawai Divisi Perencanaan dan Pengembangan Pajak dan Retribusi Daerah Badan Pendapatan Daerah Kota Pontianak serta Staff Lapangan Pengurusan BPHTB Kantor Notaris Budi Prasetiyono, S.H. Hasil analisis dari penelitian ini adalah bahwa Badan Pendapatan Daerah Kota Pontianak belum melaksanakan pengembalian kelebihan pembayaran BPHTB Tahun 2024 kepada Wajib Pajak karena pemberlakuan Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan Pemerintah Pusat dan Pemerintah Daerah yang baru diberlakukan Januari 2024. Namun, apabila dilihat dari perspektif ilmu hukum kita mengenal asas non-retroaktif. Asas non-retroaktif menyatakan bahwa hukum tidak berlaku surut, sehingga adanya pembaharuan regulasi tidak memiliki keterkaitan dengan belum direalisasikannya pengembalian kelebihan pembayaran BPHTB oleh wajib pajak Kota Pontianak.  Kata Kunci: Pengembalian Kelebihan Pembayaran BPHTB, Pajak, Kota Pontianak